Measurement of Road Safety Decade of Action Program Performance in Indonesia - Aprianto, Rizal; Syaban, Alfath Satria Negara (Jurnal Planologi, 2023)
ABSTRACT Even though the government has established the National General Plan for Road Traffic and Transportation Safety (RUNK LLAJ), questions about the effectiveness and performance measurement of this program still remain. Therefore, further research is needed to optimize traffic safety and road transportation in Indonesia. This study aims to determine how to measure the performance of the implementation of Traffic and Road Transportation safety in the National Scope, DKI Jakarta Province, and Sukoharjo Regency based on the criteria/indicators of the five Pillars and their action programs, as well as knowing the use of methods used in measuring the performance of their implementation. This research was conducted by direct observation in the field using a data collection tool in a questionnaire and analyzed using the Analytic Network Process (ANP) and Rating Scale methods. ANP is used to determine the weighting, and the Rating Scale is used to score the performance questionnaire. Based on the results of the analysis that has been carried out, it is known that the performance of the implementation of Traffic and Road Transportation safety in the National Scope is in the "GOOD" category, while in the Sukoharjo Regency, it is in the "VERY GOOD" category. Keywords: Analytic Network Process (ANP), Rating Scale, RUNK, Safety ABSTRAK Meski pemerintah telah menetapkan Rencana Umum Nasional Keselamatan Lalu Lintas dan Angkutan Jalan (RUNK LLAJ), pertanyaan tentang efektivitas dan pengukuran kinerja program ini masih ada. Oleh karena itu, penelitian lebih lanjut diperlukan untuk mengoptimalkan keselamatan lalu lintas dan angkutan jalan di Indonesia. Penelitian ini bertujuan untuk mengetahui bagaimana mengukur kinerja penyelenggaraan keselamatan Lalu Lintas dan Angkutan Jalan di Lingkup Nasional, Provinsi DKI Jakarta dan Kabupaten Sukoharjo berdasarkan kriteria/indikator lima Pilar dan program aksinya tersebut, serta mengetahui penggunaan metode yang digunakan dalam pengukuran kinerja penyelenggaraanya. Penelitian ini dilakukan dengan observasi secara langsung di lapangan menggunakan alat pengumpul data berupa kuesioner dan dianalisa menggunakan metode Analytic Network Process (ANP) dan Rating Scale. ANP digunakan untuk menentukan pembobotan dan Rating Scale digunakan untuk pemberian nilai kuesioner kinerja. Berdasarkan hasil analisa yang telah dilakukan diketahui kinerja penyelenggaraan keselamatan Lalu Lintas dan Angkutan Jalan pada lingkup Nasional adalah termasuk kategori â€œBAIKâ€, Sedangkan pada lingkup Kabupaten Sukoharjo termasuk kategori â€œSANGAT BAIKâ€. Kata kunci: Analytic Network Process (ANP), Rating Scale, RUNK, Keselamatan